To vaccinate or not to vaccinate? Dark triad personality traits in the context of decision about vaccination against COVID-19 - Badura-Brzoza, Karina; Główczyński, Patryk; Dębski, Paweł; Brzoza, Zenon (Frontiers in Psychiatry, 2025)
IntroductionThe COVID-19 pandemic and the related restrictions have changed the lives of people around the world. Compliance with the recommendations issued by the WHO and the ministries of health of individual countries was important in order to limit the transmission of the SARS-COV-2 virus. Over time, public vaccinations against COVID-19 appeared, which gave rise to a wave of anti-vaccine demonstrations.Aim of the studyBearing in mind the hypothesis about the relationship between the characteristics of the Dark Triad and pro-health behaviors, The aim of the study was to analyze the possible correlations between Dark Triad personality traits, the levels of anxiety and depressive symptoms and vaccination behavior.Material419 people participated in the study, including 317 people aged 35.87 ± 13.65 SD years who received the Covid-19 vaccination and 102 people aged 38.18 ± 12.13 SD years who decided not to receive the vaccine.MethodsThe Dirty Dozen Scale (DDS), the Perceived Stress Scale (PSS-10) and the State and Trait Anxiety Inventory (STAI-X2) were used in the study.ResultsOn the Dirty Dozen Scale, the vaccinated group had an average score of 23.29 ± 10.10 SD and the unvaccinated group had an average score of 20.81 ± 8.84 SD. Comparative analysis of the study groups showed statistically significant differences both in the overall DDS score and in its subscales - machiavellianism and narcissism. There were no differences in the psychopathy subscale. When analyzing the relationship between anxiety as a trait and stress assessed with the PSS-10 scale, no statistically significant correlations were found in the overall score on the DDS scale, as well as in the subscales of machiavellianism, psychopathy and narcissism.ConclusionsIn the study, people with features of machiavellianism and narcissism more often decided to vaccinate against COVID-19, such a relationship could not be established for people with features of psychopathy. Aversive personality traits that are part of the Dark Triad (DD) are associated with non-compliance with the imposed norms or sanitary regime related to the pandemic, but they do not exclude concern for the health of the individual. Further research is needed on the Dark Triad in the context of social and cultural differences and in the field of undertaking pro-health behaviors.